Rapid and repeatable host plant shifts drive reproductive isolation following a recent human‐mediated introduction of the apple maggot fly, Rhagoletis pomonella. (28th November 2019) - Hood, Glen R.; Powell, Thomas H. Q.; Doellman, Meredith M.; Sim, Sheina B.; Glover, Mary; Yee, Wee L.; Goughnour, Robert B.; Mattsson, Monte; Schwarz, Dietmar; Feder, Jeffrey L.
Abstract: Ecological speciation via host‐shifting is often invoked as a mechanism for insect diversification, but the relative importance of this process is poorly understood. The shift of Rhagoletis pomonella in the 1850s from the native downy hawthorn, Crataegus mollis, to introduced apple, Malus pumila, is a classic example of sympatric host race formation, a hypothesized early stage of ecological speciation. The accidental human‐mediated introduction of R. pomonella into the Pacific Northwest (PNW) in the late 1970s allows us to investigate how novel ecological opportunities may trigger divergent adaptation and host race formation on a rapid timescale. Since the introduction, the fly has spread in the PNW, where in addition to apple, it now infests native black hawthorn, Crataegus douglasii, and introduced ornamental hawthorn, Crataegus monogyna . We use this "natural experiment" to test for genetic differentiation among apple, black, and ornamental hawthorn flies co‐occurring at three sympatric sites. We report evidence that populations of all three host‐associations are genetically differentiated at the local level, indicating that partial reproductive isolation has evolved in this novel habitat. Our results suggest that conditions suitable for initiating host‐associated divergence may be common in nature, allowing for the rapid evolution of new host races when ecological opportunity arises.